Lexical-Semantic Problems and Constrains Met in Translating Qur’anic Arabic-Specific words "Nafs نفس "into English: A Cross-lingual Perspective - Alhaj, Ali Albashir Mohammed (Technium Social Sciences Journal, 2023)
This study deals with lexical -semantic problems and constrains encountered by the Quranic translators when in translating Qur’anic Arabic-Specific words '' Nafs " نفس into English. Also, the study purposes to explore uniquely three prominent translations of Qur’anic Arabic-Specific words '' nafs " نفس into English: (Abdel Haleem, 2004; Khan and AL-Hilali, 1996; Pickthall, 2001/1930) to elucidate lexical -semantic problems they encountered when rendering such Qur’anic Arabic-Specific words into the target language (English). Findings revealed that lexical -semantic problems and constrains faced in translating Qur’anic Arabic-Specific words '' Nafs " نفس into English arise from the linguistic divide resulting from the cultural differences between Arabic and English).It has also been found the inconsistencies in meaning and lexical and semantic loss would perplex and impede the Qur’an translators in translating the Noble Qur’an into English in general and Qur’anic Arabic-Specific words '' Nafs " نفس in particular. The study highlights the significance of understanding the embedded meaning in Qur’anic Arabic-specific expressions at word level when exerting exerted effort to render them into English and comprehend what the words can betoken in each specific context and then has to attempt and translate those of meaning.